Treatment of in-transit and metastatic melanoma in two patients treated with ipilimumab and topical imiquimod. Issue 4 (August 2016) - Joseph, Richard W.; Cappel, Mark; Tzou, Katherine; Bagaria, Sanjay; Gilstrap, Cheryl; Swaika, Abhisek; Jambusaria-Pahlajani, Anokhi
Abstract : Checkpoint blockade inhibitors have revolutionized the treatment of metastatic melanoma. Despite the success of these agents in improving the overall survival of patients with metastatic melanoma, not all patients achieve clinical benefit, leaving room for improvement. The presence of cutaneous metastases in patients with metastatic melanoma provides the unique opportunity to treat the cutaneous lesions with a local modality while simultaneously treating systemic disease with systemic therapy. Herein, we describe the treatment of two patients with both in-transit and metastatic melanoma with the combination of the topical toll-like receptor 7 agonist imiquimod with systemic ipilimumab. Both patients appeared to have progressed and developed new cutaneous and systemic metastases while on single agent ipilimumab only to respond when started on topical imiquimod. Both patients tolerated the combination of imiquimod and ipilimumab without serious adverse events, and both patients had excellent clinical responses. These cases provide a proof of principle of the possibility of the combination of toll-like receptor 7 agonists with immune checkpoint blockade inhibitors.